O uso de imagens de arquivo em documentários de moradias estudantis: a escrita da história do CRUSP e da moradia estudantil da UNICAMP - Oliveira, Eduardo de Souza de (2020)
The present work analyzes the appropriation of archive images by the documentaries CRUSP: um recorte (Marcelo Gutierres, 2005) and Moras à Luta (Samuel Souza and Eduardo Oliveira, 2015). The objective is to point out how the montage of heterogeneous materials, testimonies and moving images from public archives, internet videos or other films, generates private writings of the stories of the Residential Complex of the University of São Paulo (CRUSP / USP) and the Student Housing at the State University of Campinas (UNICAMP). The stories of these spaces are marked by intense student struggles and experiences, which expressed by testimony or displayed by archival image, correspond to different purposes: as a means of comparison between times and generations, in the case of CRUSP, and as collection of a historical debt, in the case of Housing.